Shifts in Chinese Dining Consumption Habits after the COVID-19 Pandemic and Future Trends in the Catering Industry - Dingova, Vendula; Šváb, Patrik; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This study explores the significant changes in China's catering industry after the COVID-19 pandemic. The pandemic sped up the digitalization of the catering industry and changed consumers' eating habits. Consumers now place greater emphasis on value for money while also pursuing high quality, and they have an unprecedented focus on food safety and hygiene. Online food delivery has transformed from an emergency option during the pandemic to a mainstream daily dining option, with significant growth in both market size and user numbers. Pre-prepared meals have also become increasingly popular among catering companies due to their standardization and cost-effectiveness. These changes have collectively driven a profound transformation in the production, distribution, and consumption patterns of the catering industry.
Vedoucí práce: Patrik Šváb
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses